2015
DOI: 10.1111/clr.12612
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peri‐implantitis: clinical outcome of chloramine as an adjunctive to non‐surgical therapy, a randomized clinical trial

Abstract: In the present randomized clinical trial of peri-implantitis therapy; non-surgical mechanical debridement with adjunctive use of a chloramine is equally effective in the reduction of mucosal inflammation as conventional non-surgical mechanical debridement up to 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…After excluding articles based on their titles and abstracts, 39 studies were left for full-text assessment. Following a discussion after full-text analysis, 18 studies were included for systematic review [9,10,12,13,16,17,19,20,23,24,26,[31][32][33][34][35][36]41]. The process of identi cation of the included studies from the initial yield is described in Fig.1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding articles based on their titles and abstracts, 39 studies were left for full-text assessment. Following a discussion after full-text analysis, 18 studies were included for systematic review [9,10,12,13,16,17,19,20,23,24,26,[31][32][33][34][35][36]41]. The process of identi cation of the included studies from the initial yield is described in Fig.1.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig.3, compared with MD alone, MD with chlorhexidine have a limited bene cial effect at 3 months following treatment. An included article reported the adjunctive effect of chloramine and found that chloramine could not improve the clinical outcomes of peri-implant diseases [31]. The effects of probiotic Lactobacillus reuteri in combination with MD were evaluated in implants with peri-implantitis, and no clinical differences between probiotic and placebo treatments were observed over time [35,36] (Fig.4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, compared to MD alone, MD with chlorhexidine has a limited beneficial effect at 3 months post-treatment. An included article reported the adjunctive effect of chloramine and found that it could not improve the clinical outcomes of periimplant diseases [31]. The effects of probiotic Lactobacillus reuteri in combination with MD were evaluated in implants with peri-implantitis, and no clinical differences between probiotic and placebo treatments were observed over time [35,36] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…23,[53][54][55] Aspects commonly assessed are pain, probing depth, mobility, bleeding index and radiographic evaluation of bone loss. 23,[54][55][56][57] Signs of peri-implant disease include bleeding or suppuration after probing, swelling, periimplant pockets greater than 4 mm, bone loss or saucer-shaped radiolucency around the implant, implant mobility and pain. 58 The diagnosis of peri-implant mucositis is generally associated with the presence of exudate release, swelling and/or bleeding on probing but without loss of bone.…”
Section: Diagnosis Of Peri-implantitismentioning
confidence: 99%